If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27x + -9 = -4 + 49 Reorder the terms: -9 + 27x = -4 + 49 Combine like terms: -4 + 49 = 45 -9 + 27x = 45 Solving -9 + 27x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 27x = 45 + 9 Combine like terms: -9 + 9 = 0 0 + 27x = 45 + 9 27x = 45 + 9 Combine like terms: 45 + 9 = 54 27x = 54 Divide each side by '27'. x = 2 Simplifying x = 2
| -4x-3+8x=21 | | 92=-4(1-3a) | | -6x+17=-6x-36+6 | | 5xn=120 | | 37+5m=-7(1-7m) | | 45+9= | | 3x+17=3+7x | | 6*5+3y=15 | | 6xy+9y=30 | | 9x+7+8x-2=90 | | x+16.45=10+15 | | 22.85+19x=21.95+18x | | X+(x+2)=1500 | | x+1+5x=19 | | 8x+2y-13=0 | | .25x+5=9 | | 190=5(3v+-7)+10v | | -2x^2+3x+14=0 | | -6(k+1)=-3-6k-3 | | 3(11r-13)=7r+57+32r | | 4+3x=x+14 | | x+15=10+16.45 | | 48-48-3(x-4)=3x | | -y-1=2y-16 | | 9x^2-45x+36=0 | | 3-0.25x=-0.5x+9 | | 75-2q=-15+4q | | -21+5(8-4)= | | .90+19x=18x | | 6x^2-54x+120=0 | | 2x-3=-3x-2 | | 2(7x-2)+7(-8-x)=-2+5+2x+5 |